Present Molecular Limitations of ON-Bipolar Cell Targeted Gene Therapy - van Wyk, Michiel; Hulliger, Elmar C.; Girod, Lara; Ebneter, Andreas; Kleinlogel, Sonja (Frontiers in Neuroscience, 2017)
Recent studies have demonstrated the safety and efficacy of ocular gene therapy based on adeno-associated viral vectors (AAVs). Accordingly, a surge in promising new gene therapies is entering clinical trials, including the first optogenetic therapy for vision restoration. To date, optogenetic therapies for vision restoration target either the retinal ganglion cells (GCs) or presynaptic ON-bipolar cells (OBCs). Initiating light responses at the level of the OBCs has significant advantages over optogenetic activation of GCs. For example, important neural circuitries in the inner retina, which shape the receptive fields of GCs, remain intact when activating the OBCs. Current drawbacks of AAV-mediated gene therapies targeting OBCs include (1) a low transduction efficiency, (2) off-target expression in unwanted cell populations and (3) a poor performance in human tissue compared to the murine retina. Here, we examined side-by-side the performance of three state-of-the art AAV capsid variants, AAV7m8, AAVBP2 and AAV7m8(Y444F) in combination with the 4×GRM6-SV40 promoter construct in the healthy and degenerated mouse retina and in human post-mortem retinal explants. We find that (1) the 4×GRM6-SV40 promoter is not OBC specific, (2) that all AAV variants possess broad cellular transduction patterns, with differences between the transduction patterns of capsid variants AAVBP2 and AAV7m8 and, most importantly, (3) that all vectors target OBCs in healthy tissue but not in the degenerated rd1 mouse model, potentially limiting the possibilities for an OBC-targeted optogenetic therapy for vision restoration in the blind.